THE DEVELOPMENT OF SPINNING WHEEL MEDIA TO TEACH VOCABULARY AT JUNIOR HIGH SCHOOL - Ayu Fatma Mufida; Widiarini Widiarini; Tyas Alhim Mubarok (PROJECT (Professional Journal of English Education), 2024)
This study focuses on the development of a spinning wheel media  for English vocabulary learning, employing the systematic Borg and Gall Research and Development (R&D) model. The spinning wheel media is designed to enhance vocabulary acquisition and address the vocabulary poverty prevalent among students. The research methodology follows the stages outlined in the Borg and Gall R&D model, including needs assessment, media development, expert validation, pilot testing, and final evaluation. Throughout these phases, data are collected, analyzed, and iteratively refined to ensure the efficacy and validity of the spinning wheel media. Initial findings from the needs analysis reveal More than 70% (21 out of 30 students) at MTs Nurul Huda Ngadirejo demonstrate shortcomings in vocabulary, affecting their proficiency in learning English. To address this issue, it's imperative to integrate additional interactive learning tools to stimulate students' engagement and elevate their participation levels. Drawing upon pedagogical theories and instructional design principles, the spinning wheel media is developed to engage students actively in vocabulary learning. The result of expert validation media and material achieved 82.55 and 95%  as a result spinning wheel media is appropriate for usage in vocabulary learning. The result of students satisfaction analysis indicates that spinning wheel is effective to increase students interest in learning vocabulary.